Influence of turbulence models on the dynamic response of a semi-submersible floating offshore wind platform. (1st October 2021) - Somoano, M.; Battistella, T.; Rodríguez-Luis, A.; Fernández-Ruano, S.; Guanche, R.
Abstract: With the aim of evaluating the effects of the selection of the wind turbulence model on the dynamic response of a semi-submersible floater supporting the DTU 10 MW RWT, we ran aero-hydro-servo-elastic simulations employing the OASIS code developed at IHCantabria. For each of the 4 sea states selected, apart from the reference case with only wave loads, we analysed 30 different realizations with coupled wind and wave loads for each of the 7 full-field turbulent winds generated by the turbulence simulator TurbSim: Kaimal and von Kármán spectral models with three different turbulence classes each and the API turbulence model. From the resulting platform motions and mooring line dynamics, it can be concluded that the selection of the wind turbulence model is not trivial. At U 0 = 5.83 m / s, the obtained results show a high dependence on the turbulence class. However, as the wind speed increases and the wind turbine achieves the rated speed, the impact of the turbulence intensity is drastically reduced, and the design tension is dominated by the thrust force and thus by the vertical wind speed profile. The highest design tension of the windward mooring lines is obtained with the API model at U 0 = 8.75 m / s (at least 357 Tm). Highlights: A mooring system cannot be designed without coupling wind loads to wave loads. Windward mooring lines tension is highly dependent on the turbulence model used. Surge displacements dominate the mooring dynamics but with non-negligible influences on heave and pitch motions. At low U0, IEC models with turbulence class A may be used to remain on the conservative side. Once the wind turbine has achieved the rated speed, the API model may be used instead to achieve higher safety levels.